Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12976-019-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the role of thrombomodulin in all-trans retinoic acid treatment of coagulation disorders in cancer patients

Abstract: Background Clinical studies have shown that all-trans retinoic acid (RA), which is often used in treatment of cancer patients, improves hemostatic parameters and bleeding complications such as disseminated intravascular coagulation (DIC). However, the mechanisms underlying this improvement have yet to be elucidated. In vitro studies have reported that RA upregulates thrombomodulin (TM) expression on the endothelial cell surface. The objective of this study was to investigate how and to what extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Retinoic acid is the bioactive metabolite of Vitamin A, which is a compound that potentially prevents or treats malignancy and which participates in multiple biological processes [29,30]. Retinoic acid can suppress the growth of cancer cells in vitro and induces cell death in breast cancer, neuroblastoma, gastric carcinoma, prostate cancer, pancreatic cancer, and acute promyelocytic leukemia cells [31][32][33]. In 2005, molecular studies showed that the trans-retinoic acid gene (ATRA) had the potential for the treatment for Wilms tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid is the bioactive metabolite of Vitamin A, which is a compound that potentially prevents or treats malignancy and which participates in multiple biological processes [29,30]. Retinoic acid can suppress the growth of cancer cells in vitro and induces cell death in breast cancer, neuroblastoma, gastric carcinoma, prostate cancer, pancreatic cancer, and acute promyelocytic leukemia cells [31][32][33]. In 2005, molecular studies showed that the trans-retinoic acid gene (ATRA) had the potential for the treatment for Wilms tumor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, coagulation abnormalities in high-risk patients with APL treated with ATRA were shown to be amenable to treatment via suppression of intrinsic mechanisms that accelerated extracellular chromatin degradation. 30 Hamed et al 31 reported that ATRA, by upregulating thrombomodulin (TM) expression on the surfaces of endothelial cells and causing oscillatory elevation of TM expression on endothelial cells during ATRA treatment, played a role in the treatment of coagulation disorders in cancer patients. All these studies demonstrated that ATRA targeted and affected the coagulation cascade reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microfluidic devices have been proposed to study the possible effects of microbubbles in microvessels [28] to represent the effects of these bubbles, which can form in the blood vessels occasionally and cause possible pathological events, such as preventing the food to reach to the cells in specific regions. Also, targeted drug delivery via nanomaterials, such as carbon nanotubes, was introduced recently and significantly increased the efficacy of the drugs [31][32][33][34]. As evaluation of these particles are highly dependent on their microenvironments, finding the optimum design point is facing some difficulties [35] and microfluidic systems can offer exceptional abilities to screen the nanoparticles to resolve these difficulties [1].…”
Section: Microfluidic Systems For Cellular Flow Manipulationmentioning
confidence: 99%